Evaluation Method of Human-Computer Interaction Effectiveness of Command and Control System Based on Eye Tracking - Tian Chenzhi, Song Min, Tian Jiwei, Xing Qinghua, Liang Wenyang (Hangkong bingqi, 2023)
The command and control system is the core support of the information warfare system. The convenience and accuracy of its operation and use directly affect the efficiency of combat command and control. In order to continuously optimize the human-computer interaction effectiveness of the command and control system, it is necessary to establish a scientific and reasonable evaluation method. This paper introduces eye movement tracking technology, uses eye movement data such as pupil diameter, number of saccades, number of fixation points, etc., to build a quantitative evaluation model of human-computer interaction search efficiency, operation efficiency, cognitive load, design complexity and attractiveness of command and control system, and uses entropy weight-variance coefficient method to weight each eye movement data to form a comprehensive evaluation result of human-computer interaction effectiveness of command and control system. Based on this method, a comparative experiment is carried out on the command and control system and the command information system, and the results of the SUS system availability scale and NASA-TLX cognitive load scale are compared and analyzed. The results verify the effectiveness and accuracy of the evaluation method.